In situ calibration of the Swarm-Echo magnetometers - R. M. Broadfoot; D. M. Miles; W. Holley; A. D. Howarth (Geoscientific Instrumentation, Methods and Data Systems, 2022)
CASSIOPE/e-POP, now known as Swarm-Echo, was launched in 2013 to study polar plasma outflow, neutral escape, and the effects of auroral currents on radio propagation in the ionosphere. The e-POP suite contains an array of eight instruments, including two fluxgate magnetometers on a shared boom. Until now, the two magnetometers relied on a set of preflight calibrations, which limited the accuracy of the magnetic field product and the magnetometers' utility for some applications. Here we present the results of an in situ calibration performed on data from 3 January 2014 to 30 January 2021 and a case study showing the improvements the calibration has made to the data utility. Periodic vector–vector calibration using the CHAOS magnetic field model results achieves an estimated root-mean-square (rms) uncertainty of 9 nT during nominal operation. This data product is now openly available through the ESA Swarm repository.